Genre de vie à l’île de Southampton d’après le journal d’un Esquimau - Hamelin, Louis-Edmond (Cahiers de géographie du Québec, 1956)
Geographical observations extracted from a diary of an Eskimo on Southamp-ton island written over a one year period, from September 1926 until October 1927. These observations are divided into two groups : those related to the winter (October-May) and those related to the summer season (June-September).